Maternal and perinatal outcomes of low-dose aspirin plus low-molecular-weight heparin therapy on antiphospholipid antibody-positive pregnant women with chronic hypertension - Long, Shangqin; Zhang, Liren; Li, Xiaodong; He, Yongjie; Wen, Xin; Xu, Nannan; Li, Xiaoqing; Wang, Jingmin (Frontiers in Pediatrics, 2023)
Abstract: Objectives: Positive antiphospholipid antibodies (aPLs) and chronic hypertension (CH) in pregnancy are important causes of maternal and neonatal morbidity and mortality. However, there are no relevant studies on the treatment of aPL-positive pregnant women with CH. This study aimed to determine the effect of low-dose aspirin (LDA) plus low-molecular-weight heparin (LMWH) on maternal and perinatal outcomes in persistently aPL-positive pregnant women with CH. Methods: Pregnant women diagnosed CH and persistently positive aPL who had no autoimmune disease such as systemic lupus erythematosus, antiphospholipid syndrome were recruited and divided into control group, LDA group and LDA plus LMWH group according to whether they use LDA and/or LMWH. A total of 81 patients were enrolled, including 40 patients in the control group, 19 patients in the LDA group, and 22 patients in the LDA plus LMWH group. The maternal and perinatal outcomes of LDA plus LMWH therapy were analysed. Results: Compared with the control group, the rate of severe preeclampsia in LDA group (65.00% vs 31.58%, p=0.016) and LDA plus LMWH group (65.00% vs 36.36%, p=0.030) had a statistically significant reduction. Compared with the control group, the rate of fetal loss in LDA group (35.00% vs 10.53%, p=0.014) and LDA plus LMWH group (35.00% vs 0.00%, p=0.002) had a statistically significant reduction. Compared with control group, the rate of live birth in LDA group (65.00% vs 89.74%, p=0.048) and LDA plus LMWH group (65.00% vs 100.00%, p=0.002) had a statistically significant increased. Compared withcontrol group, the incidence of early-onset preeclampsia (47.50% vs 36.84%, p=0.008) and early-onset severe preeclampsia (47.50% vs 13.64%, p=0.001) in the LDA plus LMWH group decreased and were statistically different. Furthermore, we also found that LDA or LDA plus LMWH hadn’t increase the rate of blood loss and placental abruption. Conclusion: Both LDA and LDA combined with LMWH could decrease the incidence of severe preeclampsia, decrease the rate of foetal loss, increase the rate of live birth. However, LDA plus LWMH could reduce and delay the onset of severe preeclampsia, prolong the gestational age and increase the rate of full-term delivery, improve the maternal and perinatal outcomes.